Fitnesskultur mellem lyst og pligt - Kirkegaard, Kasper Lund (Forum for Idræt, 2010)
Artiklen omhandler fitnesskundernes motiver til at være medlem af et fitnesscenter, hvor det viser sig at det handler både om lyst og pligt. An increasing number of physical active people are apparently choosing exercise characterized by duty rather than sports characterized by desire. This article discusses the development based on the creation of duty and desire as contradictory perceptions and extreme opposites, although they both result in restrictions and limited freedom. The intention of this article is to develop and qualify these dualistic ‘models’ of explanation. This is done through a discussion of motives and motivation and through new empirical data concerning fitness-practitioners’ own views on their exercise. Finally the concept ‘urge’ is presented as an attempt to dissolve the relation between the duty and the desire as contradictions. This can contribute to a more qualified explanation and understanding of the practitioners’ choice of fitness as a sport activity characterized by obligation.